Nanoparticle Delivery of STAT3 Alleviates Pulmonary Hypertension in a Mouse Model of Alveolar Capillary Dysplasia. Issue 7 (17th August 2021) - Sun, Fei; Wang, Guolun; Pradhan, Arun; Xu, Kui; Gomez-Arroyo, Jose; Zhang, Yufang; Kalin, Gregory T.; Deng, Zicheng; Vagnozzi, Ronald J.; He, Hua; Dunn, Andrew W.; Wang, Yuhua; et al.
Abstract : Background: Pulmonary hypertension (PH) is a common complication in patients with alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV), a severe congenital disorder associated with mutations in the FOXF1 gene. Although the loss of alveolar microvasculature causes PH in patients with ACDMPV, it is unknown whether increasing neonatal lung angiogenesis could prevent PH and right ventricular (RV) hypertrophy. Methods: We used echocardiography, RV catheterization, immunostaining, and biochemical methods to examine lung and heart remodeling and RV output in Foxf1 WT/S52F mice carrying the S52F Foxf1 mutation (identified in patients with ACDMPV). The ability of Foxf1 WT/S52F mutant embryonic stem cells to differentiate into respiratory cell lineages in vivo was examined using blastocyst complementation. Intravascular delivery of nanoparticles with a nonintegrating Stat3 expression vector was used to improve neonatal pulmonary angiogenesis in Foxf1 WT/S52F mice and determine its effects on PH and RV hypertrophy. Results: Foxf1 WT/S52F mice developed PH and RV hypertrophy after birth. The severity of PH in Foxf1 WT/S52F mice directly correlated with mortality, low body weight, pulmonary artery muscularization, and increased collagen deposition in the lung tissue. Increased fibrotic remodeling was found in human ACDMPV lungs. Mouse embryonic stem cells carrying the S52F Foxf1 mutation were used to produce chimeras through blastocyst complementation and to demonstrate that Foxf1 WT/S52F embryonic stem cells have a propensity to differentiate into pulmonary myofibroblasts. Intravascular delivery of nanoparticles carrying Stat3 cDNA protected Foxf1 WT/S52F mice from RV hypertrophy and PH, improved survival, and decreased fibrotic lung remodeling. Conclusions: Nanoparticle therapies increasing neonatal pulmonary angiogenesis may be considered to prevent PH in ACDMPV. Abstract : Supplemental Digital Content is available in the text.